2022
DOI: 10.3390/en15155574
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Meta-Analysis of Pathways to Increase Biogas Production in the Textile Industry

Abstract: The textile industry is one of the largest environmental polluters in the world. Although waste management via anaerobic digestion (AD) is a sustainable strategy to transform waste into clean energy and water recovery, the efficiency of the AD process is reduced by the presence of recalcitrant materials, chemicals, and toxic contents. This study aims to investigate the performance of several chemical, physical, and biological pretreatments applied to improve the biodegradability of textile waste. We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The maximum theoretical yield of ethanol was 92% [67]. The technological process described by Anacleto et al [67], is shown schematically in Figure 4. In the following scientific articles [9,11,28,31,32,55,58,63,69, 71÷74] alkaline NaOH, NaOH/urea, NaOH/thiourea, NaOH/urea/thiourea solutions were used for pre-treatment of textile waste.…”
Section: Literature Methods For Obtaining Ethanol (Bioethanol)mentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum theoretical yield of ethanol was 92% [67]. The technological process described by Anacleto et al [67], is shown schematically in Figure 4. In the following scientific articles [9,11,28,31,32,55,58,63,69, 71÷74] alkaline NaOH, NaOH/urea, NaOH/thiourea, NaOH/urea/thiourea solutions were used for pre-treatment of textile waste.…”
Section: Literature Methods For Obtaining Ethanol (Bioethanol)mentioning
confidence: 99%
“…SSF method were applied to obtain ethanol [2, 55, 67÷70]. The technological process described by Anacleto et al [67] is as follows: (i) in the first step, the textile waste was subjected to a bleaching process in the presence of Na2S2O4 and Na2CO3 under thermal conditions; (ii) then, the bleached textile waste was subjected to the cellulose dissolution process in the presence of H3PO4; (iii) followed the textile waste regeneration process by washing with deionised water; (iv) the next step was to remove excess water (by centrifugation) from the regenerated textile waste, followed by washing with deionised water, which was carried out 3 times; (v) the filtration step followed, from which the resulting filtration solution was neutralized with NaOH and the regenerated textile waste was collected on filter paper; (vi) the next step was to remove the salt by washing the regenerated textile waste collected by the filter paper with water; (vii) in the last step, the wet pre-treated textile waste was subjected to the SSF process, in order to obtain ethanol. Enzymatic saccharification was carried out in the presence of cellulase, and fermentation in the presence of Zymomonas mobilis, yeast extract and the following mixture of chemicals: KH 2 PO 4 , (NH4)2HPO4 and MgSO4•7H2O.…”
Section: Literature Methods For Obtaining Ethanol (Bioethanol)mentioning
confidence: 99%
See 1 more Smart Citation
“…This process also deals with different groups of microorganisms that play crucial roles in AD (Deng et al, 2020) and the syntrophic relationship between these microorganisms, which have different growth requirements (Schnürer and Jarvis, 2018;Deng et al, 2020), is mandatory to achieve maximum biogas production (He et al, 2019). Thus, many strategies have been developed to improve microbial metabolic activities and biogas production in AD, such as co-digestion, pre-treatments and upgrades approaches (Patinvoh et al, 2017;Paritosh et al, 2018;Adnan et al, 2019;Abdelwahab et al, 2020;Anacleto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%